Constitutional Analysis of Religious Moderation Policy in Serbia: Between Legal Precepts and Social Norms - Nuroniyah, Wardah; Krajišnik, Vesna; Prastiwi, Navira Shandra (Jurnal Syariah dan Hukum Komparatif, 2025)
This study examines the alignment between Serbia’s religious moderation policies and its constitutional guarantees of religious freedom, secularism, and non-discrimination. While Serbia’s 2006 Constitution enshrines these principles, the practical application of religious policies reveals discrepancies shaped by social norms and dominant religious narratives. The preferential treatment of "traditional" religious communities, especially the Serbian Orthodox Church, reflects a persistent intertwining of national identity with Orthodox Christianity. Through legal analysis and case studies, the study illustrates how cultural and institutional biases can undermine formal constitutional protections. It also explores the role of public perception, media discourse, and policy implementation in reinforcing religious hierarchies. Ultimately, the study argues that Serbia’s religious moderation remains only partially consistent with constitutional ideals, as prevailing sociocultural dynamics continue to influence both interpretation and enforcement. A more inclusive approach requires bridging legal norms with democratic values of pluralism and equal treatment for all religious communities.